Hepatoblastoma in an 18- Year Old Female; Rare Entity - Maharjan, Daisy; Gaire, Deepshikha; Adhikari, Ram Chandra (Nepalese Medical Journal, 2020)
Hepatoblastoma is a rare malignant hepatic tumor in adults. It is associated with poor prognosis as it is usually diagnosed late when the tumor is completely unresectable. Presented here, is a case of an 18-year old female with pain abdomen, vomiting, and mass over the right hypochondriac region for one month. CT scan revealed soft tissue density mass on the right lobe of liver suggestive of focal nodular hyperplasia with differential diagnosis of atypical hemangioma. Liver angiography also suggested a vascular tumor of giant hemangioma with inferior exophytic extension. The patient underwent a right extended hepatectomy. Histopathological examination revealed hepatoblastoma with predominant fetal pattern and small focal areas of embryonal pattern. The patient had an uneventful postoperative recovery and is currently undergoing chemotherapy. We present this case for its rarity and ability to masquerade other primary liver tumors in the adult age as seen in our patient.